The Conceptual-Methodological Approach to the Organizational-Economic Provision of Innovative Labor - Chernoivanova H. S. (Bìznes Inform, 2022)
The current difficult situation in the sphere of innovative labor in Ukraine causes the need for further development and deepening of research on the state of the organizational-economic provision for innovation activity and innovative labor. The purpose of the study is to substantiate the conceptual-methodological approach to the organizational and economic foundations of the provision for innovative labor. It is determined that innovation activity and innovative labor can be considered in modern conditions only in combination and represent altogether an innovative component of enterprise. To ensure the most effective management of innovations at the enterprise, conceptual provisions are developed on the organizational-economic principles of ensuring innovative labor, which are based on an integrated approach that is an integration of the process, functional, system, situational and strategic management approaches. It is concluded that the organizational-economic provision of innovative labor should take into account both the generalization of the theoretical foundations of organizational-economic provision in modern conditions, as well as the substantiation of its elements and relationships according to individual management subsystems, which must be presented in the form of a mechanism. The conceptual-methodological approach to the organizational and economic provision of innovative labor is formed, the methodological basis of which is the provisions of the modern theory of organizations, the humanistic concept of management together with the innovative paradigm and which is based on the system approach. The subjects of organizational-economic provision are innovative labor and innovative component of the enterprise. And the objects, respectively, are special requirements, as result of the transformation of which (in the process of innovation activity) an aggregate of rules and norms, tools and levers of their interaction is formed, aimed at achieving the efficiency of innovative labor.